A Study of Pronunciation Error in English Consonant - Azzatul Hadroh (FKDP (Forum Komunikasi Dosen Peneliti), 2020)
The aim of the study to find out what are the five of most English consonants which error to pronounce at second grade of MTs in Pasuruan and to find the reason what makes them the error to pronounce. The subject of the study was in the second grade of MTs. The research design was descriptive qualitative and focused on the pronounce of analysis. The findings conclude that there is eight consonant as the most mispronounce to pronounce. From the research done by the researchers, the researchers finally found eight of the 24 consonants that are difficult to pronounce, eight of which are consonants